1954
DOI: 10.1113/expphysiol.1954.sp001078
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Adrenal Gland in Homeostasis

Abstract: THE adrenal gland has a large share in maintaining the constancy of what Claude Bernard [1865] has called the "milieu interieur", serious disturbances of which lead to disease or death of the warm-blooded organism. One way of studying this share is to determine the conditions which call forth accelerated activity on the part of the gland, and to examine how an animal lacking adrenal hormones fares in the same conditions.Since the adrenal gland consists of two parts, cortex and medulla, this discussion will fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1958
1958
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…These results give further support to the suggestion that dopainine is mainly metabolized to homovanillic acid in the striatum (26,27). The conversion goes on at a faster rate (27)(28)(29) than the conversion or dopamine to norepinephrine in other sites, including the hypothalamus (29-3 1 : see alscIt the excellent review by Hornykiewicz (5)). In contrast to the eEect of longacting monoamine oxidase inhibitors, it was previously reported that the dopamine of the striatum was not increased within I or 2 h after treatment with the short-acting monoamine oxidase inhibitor harmaline, which, however, induced an increase of the serotonin in the same structure (1 3).…”
Section: Eflect Of the Combinedinj~ction Of Harmaline Andsupporting
confidence: 70%
“…These results give further support to the suggestion that dopainine is mainly metabolized to homovanillic acid in the striatum (26,27). The conversion goes on at a faster rate (27)(28)(29) than the conversion or dopamine to norepinephrine in other sites, including the hypothalamus (29-3 1 : see alscIt the excellent review by Hornykiewicz (5)). In contrast to the eEect of longacting monoamine oxidase inhibitors, it was previously reported that the dopamine of the striatum was not increased within I or 2 h after treatment with the short-acting monoamine oxidase inhibitor harmaline, which, however, induced an increase of the serotonin in the same structure (1 3).…”
Section: Eflect Of the Combinedinj~ction Of Harmaline Andsupporting
confidence: 70%
“…5 both large and small doses of hydrocortisone had the effect of reducing tolerance in adrenalectomized rats. According to Vogt (1954) the differences between the actions of hydrocortisone and cortisone are only quantitative, hydrocortisone being more active in most respects; of the two, the rat secretes mainly cortisone. It is strange therefore that cortisone failed to show any definite effect in Expt.…”
Section: Discussionmentioning
confidence: 99%
“…The adrenal glands are directly involved in metabolism (Vogt, 1954;De Silva and Wijesiriwardene, 2007). Despite the compensatory adaptations of the intact gland, it would be expected that the metabolic rate of unilaterally adrenalectomized rats will be reduced (Harvard Medical School, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In unilaterally adrenalectomized individuals, homeostatic changes may reflect not only in the endocrinology but also as somatic changes/adaptations. This is because the secretions of the adrenal glands (glucocorticoids, aldosterone and catecholamines) have long been known to be directly or indirectly implicated in the physiologic processes of metabolism and maintenance of homeostasis (Vogt, 1954;De Silva and Wijesiriwardene, 2007). Usually, changes in metabolism, either due to changes in nutritional patterns or in the endocrine system, especially the thyroid and the adrenals, are reflected as changes in the somatic weight of affected individuals (Farhana and Rehman, 2022).…”
Section: Introductionmentioning
confidence: 99%